2016
DOI: 10.1016/j.celrep.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Codon Pair Bias Is a Direct Consequence of Dinucleotide Bias

Abstract: Codon pair bias is a remarkably stable characteristic of a species. Although functionally uncharacterized, robust virus attenuation was achieved by recoding of viral proteins using underrepresented codon pairs. Because viruses replicate exclusively inside living cells, we posited that their codon pair preferences reflect those of their host(s). Analysis of many human viruses showed, however, that the encoding of viruses is influenced only marginally by host codon pair preferences. Furthermore, examination of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
160
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(169 citation statements)
references
References 29 publications
8
160
1
Order By: Relevance
“…Mice display a strong under-representation of CpG dinucleotide usage compared with Ix. scapularis , while UpA is about equally under-represented in both hosts (Simmen 2008; Kunec and Osterrieder 2016). Therefore, if POWV was adapting toward the host’s preferred codon usage, we would expect to see an increased CpG usage during replication in ticks and decreased usage in mice, as demonstrated for insect-specific and no known vector flaviviruses, respectively (Lobo et al 2009; Blitvich and Firth 2015).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Mice display a strong under-representation of CpG dinucleotide usage compared with Ix. scapularis , while UpA is about equally under-represented in both hosts (Simmen 2008; Kunec and Osterrieder 2016). Therefore, if POWV was adapting toward the host’s preferred codon usage, we would expect to see an increased CpG usage during replication in ticks and decreased usage in mice, as demonstrated for insect-specific and no known vector flaviviruses, respectively (Lobo et al 2009; Blitvich and Firth 2015).…”
Section: Resultsmentioning
confidence: 98%
“…As indicated by d N /d S ratios <1, purifying selection was very strong in mice but became quite variable ( d N /d S  = 0.1–1.5) during tick transstadial transmission. We also examined selection for host codon usage specifically based on dicucleotide bias for CpG and UpA (Kunec and Osterrieder 2016). Mice display a strong under-representation of CpG dinucleotide usage compared with Ix.…”
Section: Resultsmentioning
confidence: 99%
“…Effects on mRNA stability also can be a factor (9). In addition, recent studies suggested that codon pair bias may be a direct consequence of dinucleotide bias (10), suggesting that the increase in the frequency of CpG and UpA dinucleotides that frequently occurs with CPD may cause attenuation by inducing stronger innate immune responses (11). Regardless of the mechanism of attenuation caused by CPD, the genetic stability of live attenuated virus vaccines is paramount to avoid deattenuation, and thus, it is important to evaluate the genetic and phenotypic stability of such vaccine candidates in detail.…”
mentioning
confidence: 99%
“…Viruses mimic the codon usage profile of their respective hosts and rely largely on the chaperon apparatus of their hosts for proficient replication and enhanced robustness (Kunec and Osterrieder, 2016). In this pretext, similarity index of a concerned virus with its respective host has been suggested to be an effective tool to properly assess the impact of host genomic influence on the patterns of associated viral codonic signatures.…”
Section: Discussionmentioning
confidence: 99%